The Respiratory Chain of Plant Mitochondria: XIV. Ordering of Ubiquinone, Flavoproteins, and Cytochromes in the Respiratory Chain - Storey, Bayard T. (1972)
The effect of initial oxygen concentration on the rate and extent of oxidation of the respiratory chain carriers of anaerobic mitochondria from mung bean (Phaseolus aureus) seedlings was examined. The substrate was succinate, with malonate added to give malonate to succinate ratios of 6 to 12, thereby minimizing the flow of reducing equivalents from substrate and insuring maximal extent of oxidation of the carriers. The ratio of oxidizing equivalents available from oxygen to reducing equivalents available from reduced ubiquinone, designated the equivalents ratio, varied from 30 to 1. Cytochromes aa(3) and c(547) have unaltered oxidation half-times, designated t(½ on), as the equivalents ratio is reduced from 30 to 3, and the extent of oxidation is decreased by about 25%. The time of the oxidation-reduction cycle induced by the oxygen pulse, calculated from the point of half oxidation to that of half reduction and designated t(½ off), decreases 200 fold with this reduction in equivalents ratio. The oxidation half-time, t(½ on), for ubiquinone is unaltered by decreasing the equivalents ratio from 6 to 1; the value of t(½ off) decreases only 30% while the extent of oxidation decreases 50%. The values of t(½ on) and t(½ off) and the extent of oxidation of cytochrome b(553) and flavoprotein Fp(ha) were all much reduced at low equivalents ratios. The results, plus results from previous studies, indicate that there is the following linear sequence of components in the plant respiratory chain: Dehydrogenase·UQ·Fp(ha)·b(553)· c(549)·a·a(3) Cytochrome b(557) and the low potential flavoproteins do not fit into this linear sequence.